Artificial modifications of the coast in response to the Deepwater Horizon oil spill: quick solutions or long‐term liabilities?. Issue 1 (1st August 2011) - Martínez, M Luisa; Feagin, Rusty A; Yeager, Kevin M; Day, John; Costanza, Robert; Harris, Jim A; Hobbs, Richard J; López-Portillo, Jorge; Walker, Ian J; Higgs, Eric; Moreno-Casasola, Patricia; Sheinbaum, Julio; et al.
Abstract : The Deepwater Horizon oil spill threatened many coastal ecosystems in the Gulf of Mexico during the spring and summer of 2010. Mitigation strategies included the construction of barrier sand berms, the restriction or blocking of inlets, and the diversion of freshwater from rivers to the coastal marshes and into the ocean, in order to flush away the oil, on the premise that these measures could reduce the quantity of oil reaching sensitive coastal environments such as wetlands or estuaries. These projects result in changes to the ecosystems that they were intended to protect. Long‐term effects include alterations of the hydrological and ecological characteristics of estuaries, changes in sediment transport along the coastal barrier islands, the loss of sand resources, and adverse impacts to benthic and pelagic organisms. Although there are no easy solutions for minimizing the impacts of the Deepwater Horizon disaster on coastal ecosystems, we recommend that federal, state, and local agencies return to the strategic use of long‐term restoration plans for this region.